Penguatan Kapasitas Pengolahan Sorgum sebagai Souvenir Kuliner Desa : Pelatihan dan Pendampingan di Desa Cibiru Wetan - Muhammad Syakib Asqalani Rifai; Winda Gafrilia Prianka; Jasmine Afifa Destiani; Nur Alfi Dewi Safitri (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2025)
This Community Service activity aims to increase the capacity of sorghum (Sorghum bicolor L. Moench) processing as a culinary souvenir in Cibiru Wetan Village. Given the favorable geographical conditions and the local community's interest in food innovation, this village has excellent potential in developing sorghum-based products. This activity involves training and mentoring the community, especially mothers and teenagers, on sorghum processing techniques for food products with high selling value. In addition, this activity also focuses on developing marketing strategies and improving product quality through diversification and packaging innovation. Provisional findings show that sorghum has significant economic potential, but the community still needs to improve in processing knowledge and the technology used. Through collaboration with partners, this program succeeded in providing training, more modern processing tools, and broader market access. Thus, it is hoped that Cibiru Wetan Village can become a production center for sorghum-based products that can improve the welfare of the local community. Challenges faced include limited infrastructure and technology adaptation by the community.